2014
DOI: 10.1186/2193-1801-3-286
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate off-label use and safety

Abstract: IntroductionMethylphenidate is a piperidine derivative structurally and pharmacologically similar to amphetamine. Methylphenidate is indicated for Attention Deficit Hyperactivity Disorder (ADHD) in children aged 6 years of age and over when remedial measures alone prove insufficient. In adults, its indication, except in narcolepsy, is not defined. Methylphenidate received regulatory approval almost sixty years ago with a first registration in Switzerland in October 1954.ObjectiveTo evaluate the off-label use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 59 publications
1
16
0
Order By: Relevance
“…Psychostimulants, including methylphenidate (MPH) and amphetamine-based treatments, are the most commonly prescribed pharmacological treatments for adults and children with ADHD 1214. Despite being one of the mainstay treatments for ADHD, MPH use remains off-label for adults in some countries 15,16…”
Section: Introductionmentioning
confidence: 99%
“…Psychostimulants, including methylphenidate (MPH) and amphetamine-based treatments, are the most commonly prescribed pharmacological treatments for adults and children with ADHD 1214. Despite being one of the mainstay treatments for ADHD, MPH use remains off-label for adults in some countries 15,16…”
Section: Introductionmentioning
confidence: 99%
“…In addition, prescribing of methylphenidate to adults was not approved until 2010. It is, however, known that off-label prescribing to adults took place before the extension of the approval, 32 thus explaining why many adults are found among the users in this study and even among those who had previous use before the study period. Future research should investigate whether duration of methylphenidate use is a risk factor for overuse.…”
Section: Discussionmentioning
confidence: 79%
“…31 Off-label use has also been reported for depression and Parkinson’s disease. 32 In Sweden, only physicians with a specialization in psychiatry may prescribe methylphenidate. 29 Methylphenidate is included in the Swedish pharmaceutical reimbursement scheme, which means that the users only pay a limited proportion of the cost.…”
Section: Methodsmentioning
confidence: 99%
“…In France, 43% of reported methylphenidate adverse drug reactions are attributable to off-label prescribing (children 30%; adults 88%). 4 Modafinil is associated with psychiatric disorders, cardiovascular symptoms, and serious skin and multiorgan hypersensitivity reactions, and so on; 49% of adverse events relate to off-label prescriptions. 5 In 2011, the European Medicines Agency concluded that the benefits of modafinil could only be considered to outweigh the risks when treating narcolepsy; and recommended that other previous indications (obstructive sleep apnoea, shift-work sleep disorder and idiopathic hypersomnia) be removed from the product information.…”
Section: Adverse Side Effectsmentioning
confidence: 99%